Hubungan Antara Ketersediaan Bahan Bacaan Berbasis Kebutuhan Anak Dengan Minat Bacanya - Cindy Amelia; Setiawati Setiawati (Jurnal Family Education, 2022)
This research was motivated by the low interest in reading in TBM Kaba Cambodia Batipuh Panjang, Padang City. This is thought to be caused by the lack of availability of reading materials based on the needs of children at TBM Kaba Cambodia Batipuh Panjang, Padang City. The objectives of this study are 1) to see the description of the availability of reading materials based on the needs of children in TBM Kaba Cambodia Batipuh Panjang, Padang City. 2) to see a picture of the reading interest of the residents studying at TBM Kaba Cambodia Batipuh Panjang, Padang City. 3) to see the relationship between the availability of reading materials based on children's needs and their reading interest in TBM Kaba Cambodia Batipuh Panjang, Padang City.This research is a quantitative research with correlational type which aims to examine the correlation between the availability of reading materials and reading interest. The population in this study were 28 people, the sampling technique was cluster random sampling and taken as many as 60%, namely 17 people. Techniques in data collection using questionnaires and data collection tools in the form of a list of statements. The data analysis technique used the percentage formula and the rho sperm formula.The results of this study indicate that: 1) the description of the availability of reading materials based on the needs of children in TBM Kaba Cambodia Batipuh Panjang Padang City is categorized as incomplete. 2) the description of children's reading interest in TBM Kaba Cambodia Batipuh Panjang Padang City is categorized as low. 3) there is a significant relationship between the availability of reading materials based on children's needs and their reading interest at TBM Kaba Cambodia Batipuh Panjang, Padang City. It is hoped that the TBM manager will increase the number of reading materials according to the children's needs